INTERACTION EFFECT OF EXPLANTS TYPES AND PHYTHORMONES ON TISSUE CULTURE OF JATROPHA CURCAS SEED EMBRYO - K. C.VERMA; S. K. VERMA (The Bioscan, 2015)
Reserves of crude oil are rapidly diminishing and the reliability and security of oil supplies has been of global concern. Regenerated plantlets from embryos were separated and inoculated in MS medium supplemented with different combinations of BAP, Kinetin,IBA and 2,4 D. The results showed that 2,4 D(4.0 mg/L) was found to be more efficient for callus development in petiole(94 %) followed in leaf(90 %). The best shoot regeneration (11.5 shoots/explants) was observed in MS medium supplemented with IBA (0.4mg/L) and BAP (2.5mg/L). Root induction was successfully obtained (90-100%) in plane MS and MS fortified with auxins. Acclimatization and hardening was quite successful with survival rate of 80%.Developed regeneration protocol gives fair numbers of shoots per explants over existing protocols of jatropha.